DEMONSRATING THE KNOWLEDGE OF USING THE INTERNET RESOURCES - Kamila Turaboyeva (Лучшие интеллектуальные исследования, 2023)
Annotation: Authentic materials, like videos or songs, can be used in online lessons for designing activities for pre, while and post stages of the lesson. There are many kinds of authentic materials that a teacher can use to help students improve their language skills and keep them interested.